The Relationship Between Nomophobia and Boredom Intolerance in the Use of Social Media among Generation Z Muslim Students - Syafii, Muhammad Hisyam; Purnomo, Halim; Alberto Valero Matas, Jesus (Universitas Muhammadiyah Yogyakarta, 2024)
This study explores the relationship between nomophobia and boredom intolerance among Generation Z Muslim students who are active social media users. The increasing prevalence of smartphone dependency has been linked to anxiety disorders such as nomophobia while also exacerbating the inability to tolerate boredom, particularly in digital contexts. This study used a quantitative method with a survey approach, utilizing the Nomophobia Questionnaire (NMP-Q) and the Boredom Proneness Scale (BPS) to measure these variables among 47 randomly selected participants. The data were analyzed using simple linear regression, revealing a significant positive correlation between nomophobia and boredom intolerance: as nomophobia levels increased, tolerance for boredom decreased. This research highlights the growing concern about smartphone overreliance and its psychological effects on Generation Z. Given the crucial role of social media in the daily lives of these students, understanding the psychological dynamics at play offers insights into developing targeted interventions to reduce smartphone dependence and improve emotional regulation. The findings contribute to the broader discourse on mental health in the digital age, emphasizing the importance of fostering greater awareness of the psychological risks associated with excessive smartphone use and suggesting strategies for enhancing students' emotional resilience. Future research should investigate the cultural and social factors influencing these behaviors further to develop more effective interventions.